Can performance-based budgeting reform improve corporate environment in ESG? Evidence from Chinese-listed firms - Wang, Xueping; Hu, Shichao (Frontiers in Environmental Science, 2022)
Finance is a pillar industry of national governance. It also provides a solid guarantee for achieving the official Double Carbon target. The question of how to forefront the role of environmental governance in the reform of fiscal and taxation systems, whilst also motivating enterprises to enhance Environment in Environmental, Social, and Governance (EESG) considerations is worth investigating in depth. This study takes A-share listed companies in China from 2001 to 2020 as examples. The effect of Performance-Based Budgeting (PBB) reform on the EESG of these enterprises is empirically examined through quasi-natural experiments using a multi-time difference-in-difference model. We find that PBB significantly optimizes the EESG of the enterprises. The placebo test, the difference-in-difference method, and a series of other robustness tests all support this conclusion. Furthermore, it is suggested that the environmental governance effect of PBB is more significant in areas with heavy financial pressure and stronger government audit. The environmental governance effect of the PBB reform is significant for enterprises with government contracts, strong green innovation capabilities, or high financing constraints. The mechanism test is performed, and the results suggest that the influence mechanism of this environmental governance role lies in the fact that PBB has improved environmental protection subsidies and enhanced fiscal transparency. Through the economic consequences test, we find that enterprise EESG can bring economic benefits to enterprises, which is reflected in the improvement of enterprise return on total assets, price-to-book ratio, and total patent authorization. This study enriches literature on the economic consequences of PBB, and has significance in deepening current fiscal and tax system reform, vigorously optimizing the major strategy of carbon peak and carbon neutrality.